PENGEMBANGAN VIDEO INTERAKTIF MATERI BANGUN DATAR UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Dewi Candra Wulansari; Gamaliel Septian Airlanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to develop interactive video media at SD 3 Kaloran. The research method used is Research and Development (R&D). This research focuses on developing interactive video media to improve fourth grade mathematics learning outcomes. The research model used is the ADDIE model which has 5 process stages, namely Analysis, Design, Development, Implementation, Evaluation. The type of research used is qualitative and quantitative data. The instruments used are: (1) Documentation, (2) Questionnaire, in this research in the form of trial activities and validation sheets which are assessed by media experts, material and language experts. Based on the results of the feasibility test for media expert examiners, the expert validation sheet includes 70% material experts in the high category, 80% in the media in the high category, and 83% in the language in the very high category and is declared valid. Meanwhile, the effectiveness results were carried out using the t-test, the significance value (2-tailed) was 0.000 < 0.05. Based on the test results, interactive video media is effective and feasible in improving the learning outcomes of class IV students at SD 3 Kaloran.